The Relationship of Parenting Patterns With Student Learning Outcomes - Rukmana Esti (International Journal of Pedagogy, 2023)
Families, especially parents , give an example to their children and also give good treatment to the children in learning in order to obtain a good learning result and can achieve the desired goals, and can be useful for their families in the days to come. However, of the phenomena that occur in the field can be seen many deviations behavior of children and adolescents . One reason is the lack of parenting good parenting on children , such as failure to adequately monitor children , disciplining children are less effective, and the lack of parental affection to their children and lack of responsibility to provide for the actions of their children. This study classified quantitative descriptive correlational study. This sample is 2 Padang SMP students numbering 125 people. This research instruments such as questionnaires about parenting parents and student learning outcomes in the form of grades 1 semester of school year 2013/2014. Data were analyzed using statistical techniques Product Moment Correlation through assistance programs Microsoft Office Excel and SPSS version 16.0